Nested whole-genome duplications coincide with diversification and high morphological disparity in Brassicaceae - Walden, Nora; German, Dmitry; Wolf, Eva; Kiefer, Markus; Rigault, Philippe; Huang, Xiao-Chen; Kiefer, Christiane; Schmickl, Roswitha; Franzke, Andreas; Neuffer, Barbara; Mummenhoff, Klaus; Koch, Marcus (Nature Communications, 2020)
Angiosperms have become the dominant terrestrial plant group by diversifying for ~145 million years into a broad range of environments. During the course of evolution, numerous morphological innovations arose, often preceded by whole genome duplications (WGD). The mustard family (Brassicaceae), a successful angiosperm clade with ~4000 species, has been diversifying into many evolutionary lineages for more than 30 million years. Here we develop a species inventory, analyze morphological variation, and present a maternal, plastome-based genus-level phylogeny. We show that increased morphological disparity, despite an apparent absence of clade-specific morphological innovations, is found in tribes with WGDs or diversification rate shifts. Both are important processes in Brassicaceae, resulting in an overall high net diversification rate. Character states show frequent and independent gain and loss, and form varying combinations. Therefore, Brassicaceae pave the way to concepts of phylogenetic genome-wide association studies to analyze the evolution of morphological form and function.